Optimal Spline Approximation via ℓ0‐Minimization. (May 2015) - Brandt, Christopher; Seidel, Hans‐Peter; Hildebrandt, Klaus
Abstract Splines are part of the standard toolbox for the approximation of functions and curves in ℝd. Still, the problem of finding the spline that best approximates an input function or curve is ill‐posed, since in general this yields a "spline" with an infinite number of segments. The problem can be regularized by adding a penalty term for the number of spline segments. We show how this idea can be formulated as an ℓ0‐regularized quadratic problem. This gives us a notion of optimal approximating splines that depend on one parameter, which weights the approximation error against the number of segments. We detail this concept for different types of splines including B‐splines and composite Bézier curves. Based on the latest development in the field of sparse approximation, we devise a solver for the resulting minimization problems and show applications to spline approximation of planar and space curves and to spline conversion of motion capture data.